Odpowiedzi

2009-12-09T17:41:35+01:00
A) (-17,2)+ (-23,3)+ 13,1 + (-42,4)=(-17,2-23,3+13,1-42,4=
=(-69,8)

b) (-2,81 + (-3,2) + (1,9) + 6 +1,9= 3,79

c) (-9) + (2,7) + 0,9 + (-3,3) +6 +0= (-2,7)
1 5 1
Najlepsza Odpowiedź!
2009-12-09T17:42:32+01:00
A) (-17,2)+ (-23,3)+ 13,1 + (-42,4)= -17,2 - 23,3 + 13,1 - 42,4= -69,8

b) (-2,81 + (-3,2) + (1,9) + 6 +1,9= -2,81 - 3,2 +1,9 + 6+ 1,9 = 3,79

c) (-9) + (2,7) + 0,9 + (-3,3) +6 +0= -9 + 2,7 + 0,9 -3,3 +6 = -2,7
1 5 1
2009-12-09T17:43:32+01:00
(-17,2)+ (-23,3)+ 13,1 + (-42,4)= -40,5 +(-29,4)= -69,9
(-2,81 + (-3,2) + (1,9) + 6 +1,9= -6,01 + 1,9+7,9= -4,11+7,9=3,79
(-9) + (2,7) + 0,9 + (-3,3) +6 +0= -6,3+(-2,4)+6=-8,7+6=-1,7
1 5 1